ANALISIS KEBUTUHAN AIR BERSIH DOMESTIK DESA PINGGIRPAPAS DAERAH LAYANAN PDAM KOTA SUMENEP - Rahmanto, Ach. Desmantri; Zainah, Nor (NAROTAMA JURNAL TEKNIK SIPIL, 2024)
Pinggirpapas Village is one of the villages in Kalianget District, Sumenep Regency which consists of 3 hamlets with a total population of 5337 people. Pinggirpapas Village is a coastal area surrounded by salt fields and the Madura Strait with the majority of residents' jobs being salt transport workers, casual daily workers, salt packaging workers, fishing workers and salt farming workers. Providing clean water is very important for the people of Sumenep City. To determine the need and availability of clean water in Pinggirpapas Village, Kalianget District, Sumenep Regency in the future with a clean water system from PDAM Sumenp City. Projections of clean water needs that must be provided for the next 5 years, 10 years, 15 years, 20 years and 25 years. The data analysis techniques used in this research are projections of the number of customers, projections of public facilities, projections of the amount of water needed, Epanet analysis, and clean water distribution piping systems. Analysis of the availability of water discharge for Kalianget District for the next 5 years is 94500 l/day, for the next 10 years it is 109900 l/day, for the next 15 years it is 125300 l/day, for the next 20 years it is 140700 l/day, and for In the next 25 years it will be 156,000 l/day. The estimated need for domestic clean water production for the next 5 years is 13,801 l/day, for the next 10 years it is 16,802 l/day, for the next 15 years it is 19,802 l/day, for the next 20 years it is 22,802 l/day, and for the next 25 years in the future it will be 25803 l/day.